Aroma and bacterial communities dramatically change with storage of fresh white truffle Tuber magnatum. (November 2021) - Niimi, Jun; Deveau, Aurélie; Splivallo, Richard
Abstract: White truffles are highly valuable, but the aroma is susceptible to change with storage. How volatile composition and microbiome of Tuber magnatum evolve by storage time is poorly understood. Changes in bacterial community and volatile compounds of T. magnatum fruiting bodies with storage time at 23 °C were investigated. Truffles (21 fruiting bodies) were collected from different sites in Italy, Hungary, and Croatia. Single fruiting bodies were subsampled at four time points (day (D)0, 3, 6, and 9). Gas chromatography-mass spectrometry and microbiome composition using PCR-high throughput sequencing were used to analyse the volatiles and bacterial communities, respectively. Spoilage compounds atypical of truffles increased with storage time. Likewise, bacterial communities changed with storage time; families belonging to Xanthobacteraceae dominated at D0 and gradually evolved to more Rhizobiaceae and Pseudomonadaceae by D3 and D6, and finally with more prominent Xanthomonadaceae and Burkholderiaceae at D9. Overall, storage time had increased the diversity of bacterial communities. The microbiome and volatile data were correlated using regularised canonical correlation analysis and determined correlations between 2-methylisoborneol and five bacterial OTUs. Potential candidate bacteria and their volatile metabolites can serve as markers for truffle spoilage. The results highlighted the mechanisms by which the degradation of expensive truffles occur. Highlights: Volatile profile of Tuber magnatum changed with storage time. Trimethyl amine and 2-methylisoborneol were volatile spoilage indicators. Bacterial community increased in diversity with storage time. Five bacterial OTUs correlated with the spoilage compound 2-methylisoborneol.